2000
DOI: 10.1002/1097-0215(20001015)88:2<217::aid-ijc11>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Primary cervical carcinomas show 2 common regions of deletion at 3P, 1 within theFHIT gene: Evaluation of allelic imbalance atFHIT, RB1 andTP53 in relation to survival

Abstract: Chromosome arm 3p is re‐arranged in many tumor types, including cervical carcinomas. Putative tumor‐suppressor genes on 3p have been proposed, including the FHIT gene, which maps to chromosome band 3p14.2. We have analyzed 79 primary cervical carcinomas for allelic imbalance (AI) at 17 chromosome 3 loci, including 3 within the FHIT gene. Expression of the FHIT gene was evaluated after immunohistochemistry with an antibody against the pFHIT protein. Previously determined human papillomavirus status, defined aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Altogether, these data showed that copy number changes (homo-and hemizygous deletions and amplifications) of either NLJ3-001 or NL3-001 were detected in 29 cases (90.6%). This is significantly higher than it was reported earlier for the whole 3p -around or some more than 70% (Larson et al, 1997a;Wistuba et al, 1997;Braga et al, 1999;Helland et al, 2000). These results lend strong support to the conclusion that these two regions are really hot spots for rearrangements in CCs.…”
Section: Analysis Of Two Critical Regions In 3p213supporting
confidence: 54%
“…Altogether, these data showed that copy number changes (homo-and hemizygous deletions and amplifications) of either NLJ3-001 or NL3-001 were detected in 29 cases (90.6%). This is significantly higher than it was reported earlier for the whole 3p -around or some more than 70% (Larson et al, 1997a;Wistuba et al, 1997;Braga et al, 1999;Helland et al, 2000). These results lend strong support to the conclusion that these two regions are really hot spots for rearrangements in CCs.…”
Section: Analysis Of Two Critical Regions In 3p213supporting
confidence: 54%
“…Deletions in this region are very frequent in lung and kidney carcinomas and were also observed in a variety of other common tumors, such as breast cancer, head and neck cancer, gastrointestinal cancer, esophageal cancer, and cervical cancer (see Croce et al, 1999;Huebner and Croce, 2001;Wistuba et al, 1997;Fong et al, 1997;Greenspan et al, 1997;Muller et al, 1998;Helland et al, 2000;Zo¨chbauer-Muller et al, 2001b).…”
Section: Chromosome Region 3p142 (Fhit Gene Region)mentioning
confidence: 99%
“…Score 0 was defined as absent or lost expression, scores 1-3 were defined as markedly reduced FHIT expression and scored 4-9 were considered as normal expression. [35][36][37] …”
Section: Immunohistochemical Staining For Fhit Proteinmentioning
confidence: 99%